Morphological segmentation with tiling light sheet microscopy to quantitatively analyze the three-dimensional structures of spinal motoneurons - Huijie Hu; Dongyue Wang; Yanlu Chen; Liang Gao (Cell Regeneration)
Abstract Spinal motoneurons control muscle fibers contraction and drive all motor behaviors in vertebrates. Although spinal motoneurons share the fundamental role of innervating muscle fibers, they exhibit remarkable diversity that reflects their specific identities. Defining the morphological changes during postnatal development is critical for elucidating this diversity. However, our understanding of the three-dimensional (3D) morphology of spinal motoneurons at these stages remains limited, largely due to the lack of high-throughput imaging tools. Using tiling light sheet microscopy combined with tissue clearing methods, we imaged motoneurons of the lateral and median motor column in the cervical and lumbar cord during postnatal development. By analyzing their soma size, we found that motoneurons innervating the upper limbs differentiate into two subpopulations with distinct soma size by postnatal day 14 (P14), while differentiation of motoneurons innervating the lower limbs is delayed. Furthermore, coupling adenovirus labeling with 3D volumetric reconstruction, we traced and measured the number and lengths of dendrites of flexor and extensor motoneurons in the lumbar cord, finding that the number of dendrites initially increases and subsequently declines as dendritic order rises. Together, these findings provide a quantitative analysis of the 3D morphological changes underlying spinal motoneuron diversity.